The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Palgrave International Handbook of Youth Imprisonment 2021
DOI: 10.1007/978-3-030-68759-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated Young Men and Boys: Trauma, Masculinity and the Need for Trauma-Informed, Gender-Sensitive Correctional Care

Abstract: In this chapter we bring together three previously unconnected areas of research relating to young men and boys: trauma and prison; trauma and masculinity; and prison masculinities. Within the existing literature there emerges a significant focus on incarcerated young women and trauma, while there is a relative dearth of literature focusing on young men and boys and their trauma experiences prior to, and as a consequence of, incarceration. Furthermore, we consider the ways in which masculinity and trauma inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
2
3
0
Order By: Relevance
“…Detainees overwhelmingly indicated that their original involvement in crime derived from emotional and trauma-oriented issues which, despite a suite of offender rehabilitation programmes, remained largely unaddressed. This is consistent with recent work revealing that ‘between 62% and 98% of incarcerated young men in Australia, the United Kingdom and the United States report at least one lifetime experience of trauma prior to incarceration’ (Vaswani, Cesaroni & Maycock, 2021, p. 355). Examples varied within the current KTYJC cohort, but many involved the deprivation of food.…”
Section: Appetite For Destruction: Connecting Food To a Damaged Pastsupporting
confidence: 91%
“…Detainees overwhelmingly indicated that their original involvement in crime derived from emotional and trauma-oriented issues which, despite a suite of offender rehabilitation programmes, remained largely unaddressed. This is consistent with recent work revealing that ‘between 62% and 98% of incarcerated young men in Australia, the United Kingdom and the United States report at least one lifetime experience of trauma prior to incarceration’ (Vaswani, Cesaroni & Maycock, 2021, p. 355). Examples varied within the current KTYJC cohort, but many involved the deprivation of food.…”
Section: Appetite For Destruction: Connecting Food To a Damaged Pastsupporting
confidence: 91%
“…The findings presented in this study also highlight the traumas that characterized men’s early life-course relationships with fathers who physically and emotionally abused them, and they extend recent scholarship discussing the relationship between incarcerated men’s traumas and their masculinities (Vaswani et al, 2021). Men with lifetime traumatic experiences (LTEs) have difficulty rebuilding the relationships that offer them social support after their incarceration (Wolff et al, 2011).…”
Section: Clinical Implications and Future Directions: Developing Gend...supporting
confidence: 79%
“…High-quality mental health services are often severely lacking within correctional settings (Holsinger, 2014;Lahm, 2016), and even facilities that do have therapeutic services generally do not frequently offer systemic, relational services (Tadros, 2021;Tadros et al, 2019). Gender is one of the most important organizing principles of social life (Endendijk et al, 2018) and it should therefore not be overlooked in the development of therapeutic interventions specific to incarcerated men's needs (Sloan, 2018;Vaswani et al, 2021). Although we know that men and women need interventions that are gender responsive, incarcerated men have been largely ignored in the context of therapeutic interventions (Pettus-Davis et al, 2019).…”
Section: Clinical Implications and Future Directions: Developing Gend...mentioning
confidence: 99%
“…Previous work has suggested that masculine identity can relate to criminal attitudes and behavior, particularly among marginalized men, but less is known about masculinity among younger justice-involved males (Abrams et al, 2008). Additionally, previous research has shown that specific environments can shape masculinity (Vaswani et al, 2021) as youth form their identity in response to different social environments and lived experiences (Goodey, 1997; Griffith et al, 2012). As such, the U.S. juvenile justice system purports an emphasis on rehabilitation based on the understanding that younger individuals are still developing and thus more receptive to changing their attitudes and behaviors (Allen et al, 1975).…”
Section: Disparities Faced By Black and Latinx Youthmentioning
confidence: 99%
“…As such, the U.S. juvenile justice system purports an emphasis on rehabilitation based on the understanding that younger individuals are still developing and thus more receptive to changing their attitudes and behaviors (Allen et al, 1975). However, much of the research on masculinity in justice-involved populations has centered on how carceral environments can reinforce and perpetuate health-detracting aspects of masculinity through physical features of detention centers (Jewkes & Morrell, 2018; Miller & Najavits, 2012), daily activities in carceral programming (Abrams et al, 2008), and correctional staff interactions (Abrams et al, 2008; Vaswani et al, 2021). At the same time, research has shown that various services and interventions with young justice-involved males can help them counter the health-detracting aspects of masculinity and express alternative conceptualizations of masculinity that are more health-promoting (Abrams et al, 2008).…”
Section: Disparities Faced By Black and Latinx Youthmentioning
confidence: 99%